Can allogeneic haematopoietic cell transplantation be curative in classical Crohn's disease?. (9th November 2022) - McLaughlin, Laura; DeZoeten, Edwin; Verneris, Michael R.
Summary: The article by Moser et al. details the outcomes of 11 patients with inflammatory bowel disease (IBD) as the main manifestation of their immune deficiency syndrome who are treated with allogeneic transplantation. The authors report low rates of complications (including graft‐versus‐host disease) and resolution of symptoms. Here we outline whether allogeneic transplantation should be considered more broadly for IBD. Commentary on : Moser et al. Treatment of inborn errors of immunity patients with inflammatory bowel disease phenotype by allogeneic stem cell transplantation. Br J Haematol 2023;200:595‐607.